2013
DOI: 10.1007/s10811-013-0149-6
|View full text |Cite
|
Sign up to set email alerts
|

Anti-obesity property of the brown seaweed, Sargassum polycystum using an in vivo animal model

Abstract: Obesity has reached epidemic proportions in many countries around the world.Preventing and treating obesity is becoming an increasing priority due to dissatisfaction with high costs and hazardous side effects of anti-obesity drugs. This study was designed to investigate the anti-obesity properties of the Sabah brown seaweed, Sargassum polycystum, on body weight and blood plasma levels of rats fed a high-fat diet supplemented with different doses of the seaweed powder. Male Sprague Dawley rats were divided into… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(15 citation statements)
references
References 29 publications
0
15
0
Order By: Relevance
“…It has also been reported to have antioxidant and antiinflammatory properties (Peng, Yuan, Wu, & Wang, 2011;Sachindra et al, 2007) as well as anti-cancer activity (Kumar, Hosokawa, & Miyashita, 2013;Moghadamtousi et al, 2014). Moreover, recent studies have reported anti-obesity and antidiabetic properties associated with the consumption of fucoxanthin (Awang et al, 2014;Maeda, Hosokawa, Sashima, Murakami-Funayama, & Miyashita, 2009). Fucoxanthin therefore has considerable potential as a nutraceutical ingredient that could be incorporated into functional food and beverage products.…”
Section: Introductionmentioning
confidence: 99%
“…It has also been reported to have antioxidant and antiinflammatory properties (Peng, Yuan, Wu, & Wang, 2011;Sachindra et al, 2007) as well as anti-cancer activity (Kumar, Hosokawa, & Miyashita, 2013;Moghadamtousi et al, 2014). Moreover, recent studies have reported anti-obesity and antidiabetic properties associated with the consumption of fucoxanthin (Awang et al, 2014;Maeda, Hosokawa, Sashima, Murakami-Funayama, & Miyashita, 2009). Fucoxanthin therefore has considerable potential as a nutraceutical ingredient that could be incorporated into functional food and beverage products.…”
Section: Introductionmentioning
confidence: 99%
“…For example, feeding of seaweed powder of Sargassum polycystum suppressed weight gain in rats fed with high fat diet and reduced the plasma levels of cholesterol and triacylglycerols [20]. In another study, feeding of the brown seaweed Undaria pinnatifida showed positive effects on body weight gain, energy consumption, and serum levels of glucose and insulin in diet-induced obese mice [21].…”
Section: Seaweeds As Food and Their Potential Anti-obesity Effectsmentioning
confidence: 99%
“…We are particularly concerned with the presence of photosynthetic pigments which have curative effect against leading cause of death such as cardiovascular disease (CVD). Some studies have obviously indicated the healing power of both macroalgae [7][8][9][10][11][12] and microalgae [13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%